The Influences of School Heads Managerial Skills and Organizational Culture on Teacher Work Discipline at Vocational Schools of Lampung Indonesia - Muhammad Ihsan Dacholfany; Dewa Gde Ngurah Agung; Sabariah binti Sulaiman (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The low work discipline of teachers is influenced by the managerial effectiveness of the principal which is not maximally applied and the organizational culture that is less conducive, warranting a need for a better managerial ability of school principals and a more conducive organizational culture. This study aims to determine (1) the effect of the principal managerial skills on teacher work discipline, (2) the influence of organizational culture on teacher work discipline, and (3) the effects of principal managerial skills and organizational culture together on the work discipline of teachers in Way Kanan District Vocational High Schools, Lampung Province. A quantitative approach was used in this study to measure three variables, namely the management skills of the school principal (X 1), organizational culture (X 2), and teacher work discipline (Y). The population of this study was 374 teachers in SMKN Way Kanan district with 93 teachers as the research sample determined using the Slovin formula. The instrument used was a questionnaire that had been previously tested for validity and reliability. Data were analyzed using Regression Analysis. Based on the analysis, the following results were obtained: 1) Principal managerial influence explained 73.3% of teacher work discipline and the remaining 26.3% was other influences, 2) Organizational culture contributed 80.5% to teacher work discipline and another 19.5% was other influences, and 3) Principal managerial skills and organizational culture together contributed 84.7% to teacher work discipline and the remaining 15.3% was other influences. The conclusion is that the work discipline of SMKN teachers in the Way Kanan district will increase when good managerial skills of school principals and conducive organizational culture are applied.